Overcoming the barrier of skin to drug permeation for localized dermatological therapies - Michniak-Kohn, Bozena; Kohn, Joachim (Journal of Medical Science, 2023)
The skin’s uppermost layer, the stratum corneum is a very effective barrier against the penetration of compounds including pharmaceuticals and cosmetic actives. To deliver higher amounts of drugs into the skin layers or to deliver drugs deeper into the skin (e.g., into the dermis), several enhancement techniques have been established. These techniques include chemical penetration enhancers as well as physical techniques such as iontophoresis and microneedles. In addition, one of the newer approaches includes the use of nano-based carriers such as metallic nanoparticles and polymeric self-assembling nanospheres. This mini-review explores this new approach of using nano-based drug carriers for skin penetration enhancement. In particular we will explore the use of gold nanoparticles as well as biocompatible tyrosine-derived polymeric nanoparticles known as Tyrospheres. The most investigated carriers in the class of metallic carriers are gold nanoparticles that can be used for both medical as well as diagnostic uses. Many investigators have reported that gold nanoparticles are able to enhance the skin transport and delivery of macromolecular and hydrophilic drugs. Meanwhile, for challenging highly lipophilic and/or unstable compounds such as adapalene and Vitamin D3 packaging them into polymeric nanocarriers such as Tyrospheres enables drug delivery to hair follicles, significantly increased aqueous solubility and resulted in elevated amounts of drug in targeted skin layers. The relatively new approach of using nanotechnological approaches as a way of enhancement of drug delivery to skin shows significant promise over some other established techniques such as the addition of chemical penetration enhancers to formulations used for topical/transdermal uses.